202 Therapeutic resolution of pulmonary arterial hypertension (pah) by novel small molecule natural products. (5th June 2017) - Sharmin, N; Malik, H; Siddiqui, A; Chowdhury, H; Kanagenti, S; Graham, A; Wright, C; Morrell, N; Trembath, RC; Nasim, MT
Abstract : Heterozygous germline mutations in the gene encoding type II bone morphogenetic protein receptor (BMPRII) underlie the majority (~80%) of the familial form of pulmonary arterial hypertension (HPAH). 1 PAH is a devastating cardiovascular disorder caused by narrowing of blood vessels in the lungs. We earlier demonstrated that mutations in BMPR2 impinge upon the BMP signalling pathway and potentiate the TGF-β² signalling leading to abnormal proliferation and apoptosis resistance of endothelial and pulmonary arterial smooth muscle cells (PASMCs). 2, 3 No cure for this disorder is known. Traditional therapies aim to improve cardiopulmonary function and were established before recognising the involvement of substantial genetic components of PAH. Hence, there is an urgent need to identify novel compounds capable of providing therapeutic intervention prior to or following the onset of disease. High-throughput cell based BMP-responsive screens were carried out, which identified several natural compounds as hits. The hit compounds were optimised through a medicinal chemistry programme. These compounds were tested in a number of cell based experiments including reporter assays, gene expression studies and western blot analyses. The compounds CRT-01, CRT-02 and CRT-03 enhanced BMP signalling in BMP responsive reporter assays. Moreover, these compounds were able to induce BMP responsive id1 gene expression and increased the phosphorylation of SMAD1/5 proteins. Furthermore, these compounds inhibited excessive proliferation of PASMCs harbouring a pathogenic BMPR2 mutation. Taken together, this study identified novel compounds eliciting pro-BMP effects which may have experimental and clinical applications in PAH. References: Lane KB, Machado RD, Pauciulo MW, Thomson JR, Phillips JA, Loyd JE, Nichols WC, Trembath RC. Heterozygous germline mutations in BMPR2, encoding a TGF-Î² receptor, cause familial primary pulmonary hypertension. Nature genetics2000;26(1):81–84. Nasim MT. Ghouri A, Patel B, James V, Rudarakanchana N, Morrell NW, Trembath RC.Stoichiometric imbalance in the receptor complex contributes to dysfunctional BMPR-II mediated signalling in pulmonary arterial hypertension. Hum Mol Genet 2008;17(11);1683–94. Nasim MT, Ogo T, Chowdhury HM, Zhao L, Chen CN, Rhodes C, Trembath RC. BMPR-II deficiency elicits pro-proliferative and anti-apoptotic responses through the activation of TGFbeta-TAK1-MAPK pathways in PAH. Hum Mol Genet 2012;21(11):2548–58.